Metastatic Squamous Cell Carcinoma of Lung: An Atypical Presentation in a 65 Years Old Man (GAIMS Journal of Medical Sciences, 2023)
Lung cancer stands as one of the most prevalent and fatal malignancies worldwide. It can originate primarily in the lung or manifest as metastases from various organs within the body. Squamous cell carcinoma (SCC) metastases to the lungs account for the majority, constituting 66% of all distant metastases. Distinguishing primary lung cancers from metastatic lung tumors often relies on immuno-histochemical markers such as Napsin A and TTF-1. In this case study, we present the medical history of a 65-year-old male with a history of smoking and occupation as a farmer. He experienced a persistent cough for one year and had been grappling with breathing difficulties for the past three days. Notably, the patient had a previous diagnosis of posterior pharyngeal wall SCC and had undergone chemo-radiotherapy treatment in 2021. Regular follow-up assessments were conducted through annual PET-CT scans, with the latest revealing nodular opacities and cavitations in the left lower lobe of the lung. This article provides a comprehensive account of the histopathological findings obtained from a tiny CT-guided lung biopsy extracted from the left lower lobe mass, alongside its radiological correlation.